PENGARUH WORK-LIFE BALANCE, LINGKUNGAN KERJA, DAN ETOS KERJA TERHADAP KINERJA KARYAWAN PADA CV. FARIS COLLECTION, SIDOARJO - Farras Dwi Afiliya; Ida Aju Brahmasari (Cahaya Ilmu Bangsa, 2025)
Faris Collection is a company engaged in the field of custom convection, located at Jl. R. Suprapto, Bringin, Jiken, Tulangan District, Sidoarjo Regency. CV. Faris Collection produces various types of clothing and other school attributes. CV. Faris Collection has a company goal to become a large company that can meet consumer needs and provide the best service in partnership. Therefore, CV. Faris Collection continues to strive to improve the performance of its employees in order to be able to produce products according to consumer expectations. In the midst of efforts to face competition and meet increasing market demand, this industry requires employees with good and fast performance in producing various convection products. This study aims to analyze the effect of work-life balance, work environment, and work ethic on employee performance at CV. Faris Collection, Sidoarjo. This study is motivated by the importance of employee performance in achieving company goals, especially in the convection industry which faces tight competition and changing market dynamics. Using quantitative methods, data were collected through questionnaires distributed to 105 employees as respondents and analyzed using multiple linear regression. The analysis includes validity, reliability, classical assumptions, and hypothesis testing with the help of SPSS software. The results of the study indicate that Work-life balance has a positive and significant effect on employee performance. The work environment has a negative and significant effect on employee performance indicating the need to improve the physical and non-physical work environment. Work ethic has a positive and significant effect on employee performance. Simultaneously, the three independent variables have a significant effect on employee performance with a coefficient of determination (R²) of 72.3%, indicating that the research model is able to explain most of the variability in employee performance. The conclusion of this study is that improving work-life balance, a comfortable work environment, and a high work ethic can significantly improve employee performance. Therefore, companies are advised to pay attention to employee work-life balance, create a supportive work environment, and encourage a good work ethic to increase the company's productivity and competitiveness.